(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In 2003, the influential movement of "Hallyu" was started, and the rapid spread of telenovelas was the first success of Korean influence in the Philippines. According to Christina Flores, the "hallyu wave" started when Filipinos were deeply influenced by Korea’s telenovelas. Based on the Korean-style fashion in the Philippines (2022) Stated that Filipinos are highly adaptable when it comes to different races, cultures, and situations, and they are also susceptible to the influence of different cultures from different countries. Korean culture is one of the countries that Filipinos have admired, and according to Ahmer Glen M. Et al. (2013), Korean fans have developed not only an interest in Korean novels and Korean pop music but also an increased affinity for Korean fashion. An idea has been formed regarding this topic for being unique and informative about K-trends that influence and affect Filipinos, especially students who are interested in K-trends that impact tourism students about Korean Fashion. Researchers aim to know what the Psychological impacts of K-fashion are on Tourism students. In this study, researchers gathered information on the problems encountered by the respondents and the Psychological impact of K-fashion on tourism students. Based on the analysis of data gathering, most of the respondents are from ages 18-20 years old, with 177 participants. Also, female Tourism students are the leading respondents of this study, and the year level that got the most respondents is a second-year college with 186 respondents. Based on the gathered data, respondents encountered that accessories, clothes, shoes, makeup, and hairstyle can affect a person’s confidence, lifestyle, self- satisfaction, and also psychological thinking. On the basis of such findings, researchers recommended that educators conduct seminars and even orientation, and parents should guide their children to be mindful of following some trends like K-fashion in order for the students to know what track they are following. The support of the guardians, peers, and parents can make a big impact on the students’ psychological thinking. Also, K-fashion is one of the ways to express ourselves, giving self- satisfaction and self-worth that can affect students psychologically. Through the process of this paper, the researcher is able to see the real problem that occurred in each situation of respondents. There is a need for attention and guidance for those who are facing this kind of problem.